The Military Industrial Complex In a Developing Country: Lessons from the Republic of Turkey - Wicaksono, Tresno; Perwita, Anak Agung Banyu (Jurnal Hubungan Internasional, 2020)
Turkey is an example of a developing country concerns with the development of its defense industry. Since the early of its republican in 1923, there are many defense industry companies established, owned by both state and private sectors. Lately, Turkish defense industry development has shown significant progress by the capability to build its indigenous defense products such as tanks and ships with most local content. The current objective of the Turkish defense industry under Erdogan administrative is to establish a ‘full’ defense industry independency by 2023, precisely a hundred years of its republic age. To achieve the objective, Turkey has established its ‘defense industry structure’ similar to Eisenhower’s concept of ‘Military-Industrial Complex’. The synergy of stakeholders among the Turkish Military-Industrial Complex has led Turkey to progressively fulfill Erdogan’s objective of a ‘full’ military independency through the execution and success of its national defense projects. Therefore, by using the explanatory research method, the authors explain the existence of the Turkish Military-Industrial Complex from each role and synergy, bringing significant impacts to the state. This article argues that the development of the military industry in Turkey, covering a timeframe of 2011 to 2017, could provide valuable experiences and lessons for other developing countries to strengthen their national defense industry level.